Food security issues for low-income Hawaii residents - Hsu, L. J. Y.; Johnson, C. B.; Jokura, Y.; Rider, M.; Maddock, J. E.; Heinrich, Katie M. (My University, 2013)
Background: Support provided by the US Food Stamp Program (FSP) is intended to promote health. The objective of this qualitative study was to examine food security for low-income Hawaii residents. Methods: A sample of low-income Hawaii residents (n = 86) were recruited to participate in a series of focus group discussions. Most participants were female (73.5%), Native Hawaiian/Pacific Islander (61.6%), ages 18-39 (62.7%), high school educated (80.5%), low-income (50.6% < $10,000), used food stamps (73.5%), and had 4.07 ± 2.89 persons per household. At 2 hour focus groups, participants received a healthy meal and a monetary incentive. Audio recordings were transcribed verbatim and analyzed using NVivo. Results: Over 50% indicated FSP assistance was not enough. When this happened, most participants had alternatives including food banks, churches, friends and family members. Shopping strategies included budgeting, buying in bulk, or smarter shopping practices. Several participants were concerned about high living costs. Conclusions: Food insecurity should be addressed for FSP participants in Hawaii, with many residents not being able to meet nutritional and economic needs on their own.
Keywords: Focus groups; Food insecurity; Food stamp program; Hawaii; Low-income; Nutrition